Collaborative information integration for construction safety monitoring - Xu, Q.; Chong, Heap-Yih (John); Liao, P.C. (ELSEVIER SCIENCE BV, 2019)
Safety monitoring is a critical component of safety management. However, asymmetric safety information and inefficient communication between various stakeholders currently limit the effectiveness of safety monitoring in the construction industry. The aim of this study is to develop a holistic and collaborative information integration framework for safety monitoring that collects, analyzes, and disseminates safety information. The proposed framework provides an interconnecting platform for stakeholder communication consisting of five layers for safety monitoring: preparation layer, monitoring layer, integration layer, reporting layer, and intervention layer. To evaluate the proposed framework, a prototype system was developed and tested as a case study for building projects in Qingdao, China. The results indicate that the proposed framework and prototype were embraced by the stakeholders in the city and contributed to an improved collaborative working environment for safety inspection and monitoring in construction projects.